2011
DOI: 10.1016/j.ejpb.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and surface characteristics of gold nanoparticles influence their biodistribution and uptake by macrophages

Abstract: Spherical and rod-shaped gold nanoparticles with surface poly (ethylene glycol) (PEG) chains were characterized for size, shape, charge, poly dispersity and surface plasmon resonance. The nanoparticles were injected intravenously to 6-8 weeks old female nu/nu mice bearing orthotopic ovarian tumors and their biodistribution in vital organs was compared. Gold nanorods were taken up to a lesser extent by the liver, had longer circulation time in the blood, and higher accumulation in the tumors, compared with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
330
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(350 citation statements)
references
References 45 publications
20
330
0
Order By: Relevance
“…Hall et al reported a change in AuNP average diameter measured using DLS from 28.2 to 48.5 nm with the addition of a PEG coating. Takae et al observed an increase in nanoparticle diameter from 20 to 33.3 nm after functionalization with 6,000 M w PEG, whereas Arinda et al found that functionalization with 5,000 M w PEG increased AuNP diameter from 50 to 89 nm [30]. In the case of AuNP functionalized with 550 M w PEG, Oh et al reported that the average diameter from DLS was some 6-9 nm higher than that measured using TEM.…”
Section: Resultsmentioning
confidence: 91%
“…Hall et al reported a change in AuNP average diameter measured using DLS from 28.2 to 48.5 nm with the addition of a PEG coating. Takae et al observed an increase in nanoparticle diameter from 20 to 33.3 nm after functionalization with 6,000 M w PEG, whereas Arinda et al found that functionalization with 5,000 M w PEG increased AuNP diameter from 50 to 89 nm [30]. In the case of AuNP functionalized with 550 M w PEG, Oh et al reported that the average diameter from DLS was some 6-9 nm higher than that measured using TEM.…”
Section: Resultsmentioning
confidence: 91%
“…At the nanoscale, rod-shaped particles have been shown to exhibit higher cellular internalization (38) and such particles have been shown to exhibit excellent targeting in tumor xenografts (45). Iron oxide nanoworms and gold nanorods have been shown to induce higher tumor accumulation (46,47), and gold nanorods have been shown to exhibit reduced macrophage clearance (48). Recent studies also showed the ability of rodshaped particles to bind specifically to cancer cells in vitro (49).…”
Section: Discussionmentioning
confidence: 99%
“…Having administered AuNPs to mice p.o., Zhang et al (2010) observed a decrease in the erythrocyte count as well as the presence of nanoparticles on the surface of cellular membranes and in vesicles inside blood and marrow cells. Also, after intravenous application, gold nanoparticles have been detected in the cellular fraction of the peripheral blood of rats and in the bone marrow of mice (Arnida et al 2011, Hirn et al 2011. These observations may suggest that AuNPs affect hematopoesis and the functions of peripheral blood leukocytes.…”
mentioning
confidence: 72%
“…However, gold nanoparticles have also been found in other tissues, mainly inside phagocytes. Macrophage stimulation can contribute to the development of a systemic immune response, but before they reach target organs, AuNPs enter the bloodstream, where they can react with blood cells (Hillyer et al 2001, Sadauskas et al 2007, Sonavane et al 2008, Balasubramanian et al 2010, Lasagna-Reeves et al 2010, Arnida et al 2011, Hirn et al 2011, Thakor et al 2011, Chen et al 2013. Having administered AuNPs to mice p.o., Zhang et al (2010) observed a decrease in the erythrocyte count as well as the presence of nanoparticles on the surface of cellular membranes and in vesicles inside blood and marrow cells.…”
mentioning
confidence: 99%